Parametric analysis of co-pelletization of corncobs and algae at moderate conditions - Nakorn Tippayawong (2018)
Corn is a major crop in Thailand. After harvesting, corn residues such as corncobs are plentiful. They are usually discarded as agricultural waste. Due to their low density and non-uniform characteristics, they are hardly used as energy source. Physical upgrade via pelletization can be adopted to improve fuel quality of this agro-residue. Unless operating at excessively high pressure and temperature, corncobs are generally very difficult to form a durable and tightly packed pellet. To address this challenge, locally available algae may be mixed together with corncob in copelletizing process. In this work, densification was performed with a cylindrical die. Effects of operating parameters (die temperature of 30-80oC, compaction pressure of 100-200 MPa and algae to biomass ratio of 10-40% w/w) on pellet properties such as compact and relax densities, volumetric energy density, and compressive strength were investigated. Successful production of pellets was demonstrated at moderate compaction conditions. Die temperature, applied pressure and mixture ratio were found to have significant influence on the pellet characteristics and properties.